2013
DOI: 10.1016/j.phrs.2013.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor 1 (IGF-1) expression is up-regulated in lymphoblastoid cell lines of lithium responsive bipolar disorder patients

Abstract: Bipolar disorder (BD) is a debilitating psychiatric disease characterized by alternating episodes of mania and depression. Among mood stabilizers, lithium is the mainstay for the treatment of BD, with approximately one-third of patients showing remission from episode recurrence. While there is evidence suggesting genetic load for lithium response in BD, its molecular underpinnings are still not completely understood. To identify genes potentially involved in (or correlated with) lithium response, we carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 54 publications
3
45
0
Order By: Relevance
“…Lithium has been shown to increase the expression of the antiapoptotic gene BCL2 [4] and also to increase cAMP-responsive element-/binding protein-mediated gene transcription [5]. More recently, microarray techniques have been applied to study the effects of lithium on mouse brain [6,7], rat brain [8], and in human neuronal or peripheral blood cell lines [9,10,11,12,13]. These studies have reported effects of lithium on the expression of a number of genes involved in ion channel and receptor function, signal transduction (including the phosphatidylinositol system), neuroprotective mechanisms, endothelial growth factor, energy metabolism, and thyroid function.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium has been shown to increase the expression of the antiapoptotic gene BCL2 [4] and also to increase cAMP-responsive element-/binding protein-mediated gene transcription [5]. More recently, microarray techniques have been applied to study the effects of lithium on mouse brain [6,7], rat brain [8], and in human neuronal or peripheral blood cell lines [9,10,11,12,13]. These studies have reported effects of lithium on the expression of a number of genes involved in ion channel and receptor function, signal transduction (including the phosphatidylinositol system), neuroprotective mechanisms, endothelial growth factor, energy metabolism, and thyroid function.…”
Section: Introductionmentioning
confidence: 99%
“…The authors describe altered IGF-binding protein-2 levels as a trait-specific marker for BD, where no differences between patients with major depressive disorder and controls were found. Specific to lithium therapy, Squassina et al [44] demonstrated that IGF-1 expression is related to the response to lithium treatment in BD patients. In genome-wide expression analysis of lymphoblastoid cell lines, the IGF-1 gene was significantly overexpressed in lithium-responsive bipolar patients compared to lithium nonresponders.…”
Section: Discussionmentioning
confidence: 99%
“…Drug treatment has an important regulatory effect on the expression levels of both trophic factors [41,42]. Peripheral levels of IGF-1 were lower in patients with BD compared to patients with schizophrenia [43].…”
Section: Trophic Factorsmentioning
confidence: 98%